Case ReportBowen’s disease and basal cell carcinoma in a renal transplant recipient – case report - Wyrzykowska, Nina; Rosińska-Więckowicz, Anna; Bartoszak, Leszek; Bowszyc-Dmochowska, Monika; Żaba, Ryszard; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
The increased risk of carcinogenesis is a well-known complication in patients after transplantation. It was proved that it is mainly caused by the necessity of use of immunosuppressive drugs. The most frequent tumours are skin cancers, among which the following are the most prevalent: Kaposi's sarcoma, squamous cell carcinoma and Bowen’s disease as its in situ form, and basal cell carcinoma. Neoplastic lesions in immunosuppressed patients are characterized by their occurrence in younger patients, mainly in males, more frequent extracephalic location and formation of large tumours. Depending on the lesion location, its size and histological type, various treatment methods are used, such as cryotherapy, local application of imiquimod or 5-fluorouracil ointment, laser excision (CO2, Nd-YAG), photodynamic therapy and surgical excision. The prophylaxis includes education of patients, self-examination of the skin, avoiding sun exposure, photoprotection and actinic keratosis treatment. This article presents a case of a 60-year-old men who developed Bowen disease and basal cell carcinoma after the renal transplantation. Both skin lesions were surgically excised with a margin of healthy skin and the patient was educated about the importance of prophylaxis.